Acoustic enhancement of aerobic greywater treatment processes. (December 2021) - Chan, Jing S.; Poh, Phaik E.; Ismadi, Mohd-Zulhilmi P.; Yeo, Leslie Y.; Tan, Ming K.
Abstract: Increasing the efficiency of aerobic greywater treatment is crucial to ensure that greywater recycling can be effectively implemented in individual and community households. In this work, we demonstrate that exposing greywater samples to low intensity high frequency (MHz-order) surface acoustic waves (SAWs) during the aerobic treatment process can result in increases in the total suspended solids (TSS), chemical oxygen demand (COD) and biochemical oxygen demand (BOD) removal efficiencies by 24%, 24% and 21%, respectively, over a 2 h aerobic digestion period, and up to 37% (TSS removal efficiency) over a 4 h period compared to the unexposed controls. These values are considerably higher than that typically obtained with lower frequency (kHz-order) bulk ultrasound, particularly because the SAW does not cause denaturation of bacteria in the greywater suspension unlike its low frequency counterpart. The SAW enhancement in removal efficiencies can primarily be attributed to the acoustic radiation pressure and acoustic streaming that it generates, which act to efficiently deagglomerate the bacterial flocculates in addition to promoting more uniform mixing of the suspended waste, bacteria and dissolved oxygen in the sample. Also, the results indicate that in the presence of air bubbles in the greywater, the MHz-order SAW treatment remains effective. Additionally, we show that it is possible to further increase the TSS removal efficiency by about twofold through a hybrid process. This ability to significantly accelerate the rate of aerobic digestion to achieve a given removal efficiency level highlights the potential of this novel low-cost technology for improving domestic greywater treatment. Graphical abstract: Unlabelled Image Highlights: MHz-order surface acoustic waves can provide continuous greywater treatment without inflicting damage to bacteria. Increase in total suspended solids removal efficiency of up to 29% after 2 h aerobic treatment. Up to 37% increase in total suspended solids removal efficiency after 4 h aerobic treatment. The increase in total suspended solids (TSS) removal efficiency can be maintained with higher initial TSS concentrations. Hybrid kHz-order pre-treatment and MHz-order continuous treatment can lead to a twofold increase in TSS efficiency.